ANALISIS KINERJA TATA KELOLA TEKNOLOGI INFORMASI PADA PERPUSTAKAAN XYZ MENGGUNAKAN FRAMEWORK COBIT 5.0 - Yanuar Wicaksono; Denis Ariski; Tri Rochmadi; Raden Nur Rachman Dzakiyullah (Universitas Alma Ata, 2025)
The use of information technology in organizations, including government agencies, is crucial for improving efficiency and service quality. XYZ Library utilizes information technology in various aspects of its operations, thus requiring an analysis of information technology governance to ensure optimal utilization. This study aims to analyze the performance of information technology governance at XYZ Library using the COBIT 5.0 Framework, focusing on the Deliver, Service, and Support (DSS) and Monitor, Evaluate, and Assess (MEA) domains. The research method used is a qualitative descriptive method, with data collection through interviews, observations, and questionnaires. The analysis was conducted to measure the level of capability of the DSS and MEA domains and identify gaps (GAP) between the current state (as-is) and the expected state (to-be). The results show that four of the five domains are at levels 4 or 3, with a GAP of 1 level from the expected target. DSS01, MEA02, and MEA03 show fairly consistent processes but still need improvement in terms of innovation, documentation, and compliance audits. Meanwhile, the DSS02 and MEA01 domains still require improvement in terms of documentation and incident evaluation procedures, as well as system performance. This study provides strategic recommendations aimed at strengthening information technology governance at the XYZ Library on a sustainable basis in the future.